Copper alloy sheet material and drawn part
By optimizing the alloy composition of copper alloy sheets and the azimuth density of β-fiber, the shortcomings of existing copper alloy sheets in depth drawing processability, mechanical strength and electrical conductivity are solved, and high-performance copper alloy sheets are achieved.
Patent Information
- Application Number
- CN202380053496.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-13
- Filing Date
- 2023-04-26
- Publication Date
- 2025-02-14
AI Technical Summary
Existing copper alloy sheets have shortcomings in depth drawing processability, mechanical strength and conductivity, especially the low average azimuth density of β-fiber, resulting in poor depth drawing processability.
By optimizing the alloy composition, it contains 0.10%~1.00% Cr, the remaining part is Cu and impurities, and the average azimuth density value of β-fiber was measured by EBSD method, and the tensile strength in the parallel direction of the rolling is controlled between 6.0~10.0. Between 420 MPa ~ 700 MPa, the conductivity is between 65% IACS ~ 90% IACS.
It realizes excellent depth drawing processability, sufficient mechanical strength and high conductivity of copper alloy sheets, and is suitable for high-performance connectors and heat dissipation parts.
Smart Images

Figure CN119452113A_ABST
Abstract
Description
Technical Field
[0001] This case involves a copper alloy sheet and deep-drawn parts. Background Art
[0002] In recent years, with the advancement of high performance in various fields, high drawability has been required for parts to be drawn.
[0003] For example, Patent Document 1 describes a copper alloy plate in which the KAM value of a Cu-Cr-Sn-Zn alloy and the orientation density of β-fiber are controlled within a predetermined range to reduce residual stress and improve etching characteristics.
[0004] However, Patent Document 1 does not mention the deep drawing workability of the copper alloy plate. In addition, in Patent Document 1, the upper limit of the maximum value of the orientation density of β-fiber is specified, while on the other hand, the lower limit of the maximum value of the orientation density of β-fiber is not specified. In addition, in Patent Document 1, no step is implemented to increase the average value of the orientation density of β-fiber in the manufacture of the copper alloy plate, and a melt treatment is performed. For this reason, we speculate that the average value of the orientation density of β-fiber is low, so we think that the deep drawing workability is low. In addition, in Patent Document 1, tension leveling is performed in the manufacture of the copper alloy plate, so the KAM value is low and the mechanical strength is also low.
[0005] [Prior Technical Literature]
[0006] (Patent Document)
[0007] Patent Document 1: Japanese Patent Application Publication No. 2013-194246 Summary of the invention
[0008] [Problems that the invention aims to solve]
[0009] The present invention aims to provide a copper alloy sheet material having excellent drawability and sufficient mechanical strength and electrical conductivity, and a drawn part using the copper alloy sheet material.
[0010] [Technical means to solve the problem]
[0011] [1] A copper alloy plate having an alloy composition, wherein the alloy composition contains 0.10 mass % or more and 1.00 mass % or less of Cr, the balance of which is Cu and unavoidable impurities, and wherein the β-fiber (Φ 2=45° to 90°) is 6.0 or more and 10.0 or less, the tensile strength in the direction parallel to the rolling is 420 MPa or more and 700 MPa or less, and the electrical conductivity is 65% IACS or more and 90% IACS or less.
[0012] [2] The copper alloy sheet material according to [1] above, wherein the maximum value of the orientation density of the β-fiber is 9.0 or more.
[0013] [3] The copper alloy sheet material according to [1] or [2] above, wherein the average KAM value measured by the EBSD method is 0.5° or more and 2.0° or less.
[0014] [4] A copper alloy sheet material as described in any one of [1] to [3] above, wherein the area ratio of a region having atomic planes whose normal to the (100) plane forms an angle of less than 10° with the normal to the plate surface of the copper alloy sheet material as measured by the EBSD method is 10% or less.
[0015] [5] A copper alloy sheet material as described in any one of [1] to [4] above, wherein the alloy composition further contains a total of 0.10 mass % or more and 1.00 mass % or less of one or more elements selected from the group consisting of Mg, Sn, Zn, Fe, Si and Zr.
[0016] [6] The copper alloy sheet material according to any one of [1] to [5] above, wherein the copper alloy sheet material is a copper alloy sheet material for drawing.
[0017] [7] A drawn part using the copper alloy sheet material described in any one of [1] to [6] above.
[0018] [effect]
[0019] According to the present invention, it is possible to provide a copper alloy sheet material having excellent drawability and having sufficient mechanical strength and electrical conductivity, and a drawn component using the copper alloy sheet material. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is an example of a crystal orientation distribution map of a copper alloy plate obtained by EBSD measurement and grain orientation distribution function analysis. DETAILED DESCRIPTION
[0021] The following describes the implementation in detail.
[0022] As a result of repeated research efforts by the present inventors, the following facts were discovered and the present case was completed in accordance with such a technical idea: having a predetermined alloy composition and performing a step of increasing the orientation density of β-fiber to control the average value of the orientation density of β-fiber at a relatively high level, the copper alloy sheet has excellent deep drawability and sufficient mechanical strength and conductivity.
[0023] The copper alloy sheet of the embodiment has an alloy composition containing 0.10% by mass or more and 1.00% by mass or less of Cr, and the balance is Cu and unavoidable impurities. The average value of the orientation density of β-fiber (Φ 2 = 45° to 90°) measured by the EBSD method is 6.0 or more and 10.0 or less, the tensile strength in the rolling parallel direction is 420 MPa or more and 700 MPa or less, and the conductivity is 65% IACS or more and 90% IACS or less.
[0024] First, the alloy composition of the copper alloy sheet will be described.
[0025] The copper alloy sheet of the above embodiment has an alloy composition containing 0.10% by mass or more and 1.00% by mass or less of Cr, and the balance is Cu and unavoidable impurities.
[0026] <Cr: 0.10% by mass or more and 1.00% by mass or less>
[0027] Cr (chromium) is an element required to increase the strength of the copper alloy sheet, and it is necessary to contain 0.10% by mass or more and 1.00% by mass or less of Cr. If the content of Cr is 0.10% by mass or more, the mechanical strength of the copper alloy sheet increases. In addition, if the content of Cr is 1.00% by mass or less, the generation of coarse second phases is suppressed, and thus the deep drawability is improved. Coarse second phases are likely to become the starting points of cracks during deep drawing. Therefore, the lower limit value of the content of Cr is 0.10% by mass or more, preferably 0.20% by mass or more, and more preferably 0.30% by mass or more. In addition, the upper limit value of the content of Cr is 1.00% by mass or less, preferably 0.80% by mass or less, and more preferably 0.70% by mass or less.
[0028] <Sub-components of the copper alloy sheet: 0.10% by mass or more and 1.00% by mass or less>
[0029] The alloy composition of the copper alloy sheet can further contain one or more elements selected from the group consisting of Mg, Sn, Zn, Fe, Si, and Zr in a total amount of 0.10% by mass or more and 1.00% by mass or less. In other words, in addition to the necessary basic component, that is, Cr, the copper alloy sheet can further contain one or more components selected from the group consisting of Mg, Sn, Zn, Fe, Si, and Zr in a total amount of 0.10% by mass or more and 1.00% by mass or less as optional components, that is, sub-components.
[0030] <Mg: 0.10% by mass or more and 0.30% by mass or less>
[0031] If the content of Mg (magnesium) is 0.10% by mass or more, the stress relaxation resistance characteristics of the copper alloy sheet can be improved. If the content of Mg is 0.30% by mass or less, a decrease in the conductivity of the copper alloy sheet can be suppressed. Therefore, the lower limit value of the content of Mg is preferably 0.10% by mass or more, and the upper limit value of the content of Mg is preferably 0.30% by mass or less.
[0032] <Sn: 0.10% by mass or more and 0.30% by mass or less>
[0033] If the content of Sn (tin) is 0.10% by mass or more, the stress relaxation resistance characteristics of the copper alloy sheet can be improved. If the content of Sn is 0.30% by mass or less, a decrease in the conductivity of the copper alloy sheet can be suppressed. Therefore, the lower limit value of the content of Sn is preferably 0.10% by mass or more, and the upper limit value of the content of Sn is preferably 0.30% by mass or less.
[0034] <Zn: 0.10% by mass or more and 0.50% by mass or less>
[0035] If the content of Zn (tin) is 0.10% by mass or more, the adhesion and migration characteristics of tin plating can be improved. If the content of Zn is 0.50% by mass or less, a decrease in the conductivity of the copper alloy sheet can be suppressed. Therefore, the lower limit value of the content of Zn is preferably 0.10% by mass or more, and the upper limit value of the content of Zn is preferably 0.50% by mass or less.
[0036] <Fe: 0.05% by mass or more and 0.30% by mass or less>
[0037] When the content of Fe (iron) is 0.05 mass% or more, the grain growth after dynamic recrystallization during hot rolling can be inhibited, and the surface roughness of the deep-drawn parts can be suppressed. When the content of Fe is 0.30 mass% or less, the generation of coarse Fe-containing precipitates during casting is inhibited, so the deep drawability is improved. Coarse Fe-containing precipitates are likely to become the starting points of cracks during deep drawing. Therefore, the lower limit value of the content of Fe is preferably 0.05 mass% or more, and the upper limit value of the content of Fe is preferably 0.30 mass% or less.
[0038] <Si: 0.02 mass% or more and 0.40 mass% or less>
[0039] When the content of Si (silicon) is 0.02 mass% or more, Si compounds are formed with other additive elements, such as Mg and Cr, and the strength of the copper alloy sheet increases. When the content of Si is 0.40 mass% or less, the decrease in the thermal conductivity of the copper alloy sheet can be suppressed, and sufficient heat dissipation can be obtained. Therefore, the lower limit value of the content of Si is preferably 0.02 mass%, and the upper limit value of the content of Si is preferably 0.40 mass%.
[0040] <Zr: 0.05 mass% or more and 0.30 mass% or less>
[0041] When the content of Zr (zirconium) is 0.05 mass% or more, the grain growth after dynamic recrystallization during hot rolling can be inhibited, and the surface roughness of the deep-drawn parts can be suppressed. When the content of Zr is 0.30 mass% or less, the generation of coarse Zr-containing precipitates during casting is inhibited, so the deep drawability is improved. Coarse Zr-containing precipitates are likely to become the starting points of cracks during deep drawing. Therefore, the lower limit value of the content of Zr is preferably 0.05 mass% or more, and the upper limit value of the content of Zr is preferably 0.30 mass% or less.
[0042] <The balance: Cu and unavoidable impurities>
[0043] The balance other than the above components is Cu (copper) and unavoidable impurities. Unavoidable impurities mean impurities of a content level that are inevitably mixed in during the manufacturing process. Although it varies depending on the content of unavoidable impurities, it may sometimes be the main cause affecting the properties of the copper alloy sheet. Therefore, the content of unavoidable impurities is preferably small. Examples of unavoidable impurities include non-metallic elements such as S (sulfur), C (carbon), and O (oxygen); and elements such as Sb (antimony). Furthermore, the upper limit value of the content of unavoidable impurities is preferably 500 ppm or less for each of the above elements, and preferably 2000 ppm or less for the total of the above elements.
[0044] Next, the tensile strength of the copper alloy sheet will be described.
[0045] The tensile strength of the copper alloy sheet in the direction parallel to the rolling (hereinafter also referred to as tensile strength) is greater than 420 MPa and less than 700 MPa. If the tensile strength of the copper alloy sheet is greater than 420 MPa, the strength can be improved. Therefore, the copper alloy sheet is more suitable for module housings and connectors that require high strength. As mentioned above, the greater the tensile strength of the copper alloy sheet, the more preferred. For example: the tensile strength of the copper alloy sheet is greater than 420 MPa, preferably greater than 500 MPa, and more preferably greater than 600 MPa. In addition, the tensile strength of the copper alloy sheet is, for example, less than 700 MPa.
[0046] The tensile strength of the copper alloy sheet material can be measured in the following manner: Based on JIS Z 2241:2011, a tensile test is performed on the copper alloy sheet material in a direction parallel to the rolling direction using a No. 13B test piece.
[0047] Next, the electrical conductivity of the copper alloy plate will be described.
[0048] The electrical conductivity of the copper alloy sheet is greater than 65% IACS and less than 90% IACS. If the electrical conductivity of the copper alloy sheet is greater than 65% IACS, the Joule heat during power-on can be reduced. In addition, the electromagnetic wave shielding can be improved. Thermal conductivity can be calculated from the electrical conductivity by the Wiedemann-Franz law, and it is known that if the temperature is constant, it will be in a proportional relationship with the electrical conductivity and will not vary depending on the type of metal. Therefore, if the electrical conductivity of the copper alloy sheet increases, the heat dissipation of the copper alloy sheet can be improved. Therefore, if the electrical conductivity of the copper alloy sheet is greater than 65% IACS, the copper alloy sheet is more suitable for connectors that pass high currents, and module housings that require high electromagnetic wave shielding and thermal conductivity. In addition, the upper limit of the electrical conductivity of the copper alloy sheet is, for example, less than 90% IACS.
[0049] The electrical conductivity of the copper alloy sheet can be measured by the four-terminal method.
[0050] Next, the azimuthal density of β-fiber in the copper alloy plate will be described.
[0051] For copper alloy plates, the β-fiber (Φ 2=45°~90°) (hereinafter also referred to as the average value of the azimuthal density of β-fiber) is 6.0 or more and 10.0 or less. If the average value of the azimuthal density of β-fiber in the copper alloy sheet is within the above range, the uniformity of the shape of the drawn part can be improved. If the average value of the azimuthal density of β-fiber is less than 6.0, the apex height of the undulations (ears, flanges) of the drawn part is reduced, resulting in that it is not easy to form a flange during forward pressurization. In addition, if the average value of the azimuthal density of β-fiber exceeds 10.0, there is a problem that the anisotropy of the mechanical properties of the copper alloy sheet becomes stronger, which becomes a limitation of the pressurization design when the copper alloy sheet is drawn. From the above reasons and the viewpoint of making the shape of the drawn part uniform, the average value of the azimuthal density of β-fiber in the copper alloy sheet is 6.0 or more and 10.0 or less, preferably 7.0 or more and 10.0 or less, and more preferably 8.0 or more and 10.0 or less.
[0052] In addition, the β-fiber (Φ 2 =45°~90°) (hereinafter also referred to as the maximum value of the orientation density of β-fiber) is preferably 9.0 or more. If the maximum value of the orientation density of β-fiber of the copper alloy sheet is 9.0 or more, the orientation degree of the specific crystal orientation of β-fiber is improved, and the uniformity of the shape of the drawn product is easily improved.
[0053] The so-called orientation density, also expressed as crystal orientation distribution function (ODF), is used to quantitatively analyze the existence ratio and dispersion state of the crystal orientation of the aggregate structure. The orientation density is calculated by the crystal orientation distribution analysis method using the series expansion method based on the measurement data of three or more positive pole diagrams such as (100) positive pole diagram, (110) positive pole diagram, and (111) positive pole diagram, using EBSD and X-ray diffraction measurement results.
[0054] Next, the average KAM value of the copper alloy plate is explained.
[0055] Regarding the average KAM value (hereinafter also referred to as the average KAM value) measured by the EBSD method in the copper alloy sheet, the lower limit is preferably 0.5° or more, more preferably 0.6° or more, and further preferably 0.7° or more, and the upper limit is preferably 2.0° or less, more preferably 1.9° or less, and further preferably 1.8° or less. If the average KAM value of the copper alloy sheet is 0.5° or more and 2.0° or less, the balance between the corner R and the material strength during drawing is good. Specifically, if the average KAM value of the copper alloy sheet is 0.5° or more, the material strength is improved. In addition, if the average KAM value of the copper alloy sheet is 2.0° or less, it is easy to make the corner R smaller during drawing.
[0056] The so-called KAM (Kernel Average Misorientation) value refers to the average value of the crystal orientation difference between the measurement point and all adjacent measurement points. The KAM value is related to the dislocation density and corresponds to the lattice strain of the crystal.
[0057] In the measurement and analysis of crystal orientation by EBSD measurement, the analysis of β-fiber orientation density is performed using the EBSD (Electron BackScatter Diffraction) method. The so-called EBSD method refers to a crystal orientation analysis technology that uses the reflected electron Kikuchi line diffraction generated after irradiating the sample, that is, the copper alloy plate, with an electron beam in a scanning electron microscope (SEM). The measurement part is a surface parallel to the rolling direction of the copper alloy plate (the main surface of the copper alloy plate) set as the surface after mirror finishing by electrolytic polishing, and the measurement area is set to 500 μm×500 μm (250000 μm 2), the scanning is set to 0.2 μm in order to measure fine grains, and EBSD measurement is performed. Furthermore, the measurement surface can be a section parallel to the rolling direction. At this time, mechanical grinding is performed, and the surface is exposed by polishing with colloidal silica, and then 500 μm×plate thickness is measured. β-fiber and KAM values can be obtained from the EBSD measurement results by analysis. The electron beam is a field emission electron gun of a field emission scanning electron microscope as the generation source. The probe diameter during the measurement is set to about 0.015 μm. The analysis software uses OIM Analysis7 (trade name) manufactured by TSL Solutions Co., Ltd. The information obtained in the analysis of grains by EBSD includes information about the penetration of the electron beam into the copper alloy plate material to a depth of 10 nm from the surface. In addition, in the analysis, the orientation difference of 5° or more is defined as the grain boundary, the measurement point with a reliability index CI value of 0.1 or more and the grain composed of 2 pixels or more are set as the object of analysis, and the Tolerance angle is set to 10°. Furthermore, analysis of the area ratio of crystal orientations includes equivalent orientations.
[0058] Figure 1 This is an example of a crystal orientation distribution map of a copper alloy sheet material measured by EBSD and analyzed by crystal orientation distribution function (ODF: crystal orientation distribution function). Figure 1 The crystal orientation distribution diagram of the copper alloy plate is expressed in terms of the Euler angles of the three directions of the two orthogonal directions in the rolling surface, that is, the direction RD parallel to the rolling direction and the plate width direction TD, and the normal direction ND of the rolling surface. The azimuth rotation of the RD axis is Φ, and the azimuth rotation of the ND axis is Φ. 1 、Set the azimuth rotation of the TD axis to Φ 2 .
[0059] When the crystal orientation is expressed in Euler angles, Φ 2 The average value of the ODF intensity when the range of φ is 45 to 90° and the random orientation sample is used as the reference is set as the average value of the orientation density of β-fiber measured by the EBSD method. 2 The maximum value of the ODF intensity when the range of is 45 to 90° and the sample with random orientation is used as a reference is set as the maximum value of the orientation density of β-fiber measured by the EBSD method.
[0060] In addition, the average value of the KAM values of all the analysis target points in the measurement area is set as the average KAM value measured by the EBSD method.
[0061] In addition, the area ratio of the region of the atomic plane having the angle of less than 10° between the normal line of the (100) plane and the normal line of the plate surface (main surface) of the copper alloy sheet measured by the EBSD method (hereinafter referred to as the area ratio within 10°) is preferably 10% or less, and more preferably 8% or less. That is, in the crystal orientation analysis of the EBSD method, with respect to the aggregation of the atomic planes in the direction of the plate surface normal line of the copper alloy sheet, the area ratio of the measurement points where the angle difference between the normal line of the (100) plane of the crystal and the plate surface normal line of the copper alloy sheet is less than 10° in all the measurement points (measurement area) is preferably 10% or less, and more preferably 8% or less. If the above-mentioned area ratio is less than 10%, the uniformity of the shape of the drawn part (uniformity of undulation) can be improved. In addition, the standard deviation of the vertex height in the undulation of the edge of the cylindrical drawn part can be reduced. As a result, the variation of the length of the flange during forward pressurization can be suppressed, and the effects of improved positioning and improved yield due to fracture can be obtained.
[0062] The copper alloy sheet material of the embodiment is suitable as a copper alloy sheet material for drawing because of its excellent deep drawing properties, mechanical strength, and heat dissipation. The drawn parts formed by deep drawing the copper alloy sheet material before deep drawing, that is, the copper alloy sheet material for deep drawing, that is, the drawn parts using the copper alloy sheet material are suitable for: connectors for electronic equipment, lead frames, relays, switches, sockets, shielding shells, shielding cans, camera modules, heat dissipation parts for liquid crystal and organic EL displays, batteries, MEMS (micro-electromechanical systems) microphones and other MEMS element shells, automotive connectors, etc. Among them, it is suitable for: the clamping material and shell of the connector requiring high heat dissipation, the camera module shell, the battery shell, the shielding shell, and the shell of the vibration element.
[0063] Next, an example of a method for manufacturing the copper alloy sheet material of the above embodiment is described. The copper alloy sheet material of the above embodiment can be manufactured by sequentially performing reheating [step 2], hot rolling [step 3], warm rolling [step 4], cooling [step 5], cold rolling [step 6], aging heat treatment [step 7], cold rolling [step 8], and low temperature annealing [step 9] on the ingot having the above alloy composition obtained by melt casting [step 1]. No solution treatment and tension leveling are performed. In addition, reheating [step 2], hot rolling [step 3], warm rolling [step 4], and cooling [step 5] are performed continuously. The surface oxide film generated by the continuous steps of reheating [step 2], hot rolling [step 3], warm rolling [step 4], and cooling [step 5] can be appropriately removed by plane cutting before cold rolling [step 6].
[0064] In the melting and casting [step 1], the copper alloy ingot having the above alloy composition is obtained by melting the alloy components and casting. For example, the melting is performed in the air using a high-frequency melting furnace. The type of alloy components, casting conditions, etc. are appropriately set.
[0065] Reheating [step 2], hot rolling [step 3], warm rolling [step 4], and cooling [step 5] are composed of four consecutive basic steps, and the four consecutive basic steps are composed of the following: reheating of the copper alloy ingot in a reheating furnace at a predetermined temperature for a predetermined time to homogenize it [step 2]; hot rolling accompanied by dynamic recrystallization just after the heat treatment [step 3]; warm rolling without dynamic recrystallization after hot rolling [step 4]; cooling just after warm rolling [step 5].
[0066] In the reheating [step 2], the copper alloy ingot is heat treated in a temperature range of 990°C to 1050°C for 1 hour to 10 hours. When the heat treatment temperature is less than 990°C, the material temperature in the warm rolling [step 4] is likely to decrease, and the desired effect in the warm rolling [step 4] cannot be obtained. When the heat treatment temperature exceeds 1050°C, the grain boundary becomes weak, and cracks are likely to occur during the hot rolling [step 3].
[0067] Hot rolling [step 3] accompanied by dynamic recrystallization is performed just after reheating [step 2]. Hot rolling [step 3] can be performed as long as it is accompanied by dynamic recrystallization. For example: hot rolling is performed between the reheating temperature and 750°C in such a way that the processing rate calculated from the thickness before the start of rolling and the thickness after the first operation that has been completed until 750°C is 50% or more. When dynamic recrystallization does not occur sufficiently, it is easy to become an uneven structure. The material temperature during hot rolling can be measured with a radiation thermometer.
[0068] After hot rolling [step 3], warm rolling [step 4] is performed, and rolling is continued without dynamic recrystallization. In warm rolling [step 4], the material temperature is between 700°C and 500°C, and the processing rate calculated from the thickness before the first operation at 700°C and the thickness after the first operation at 500°C is 50% or more. The material temperature during warm rolling can be measured by a radiation thermometer. Under this condition, crystal rotation can be promoted, and the orientation density of β-fiber can be increased, thereby improving the deep drawing workability. If rolling is performed at a temperature higher than 700°C, dynamic recrystallization may occur, and there is no effect of increasing the orientation density of β-fiber. If rolling is continued until the temperature does not reach 500°C, the precipitates tend to grow coarse, so there is a tendency that the material strength will be impaired; and the (100) plane that impairs the shape uniformity of the deep drawing part will eventually be oriented on the plate surface. Furthermore, when the processing rate is less than 50%, the orientation density of β-fiber decreases.
[0069] After warm rolling [step 4], cooling [step 5] is performed. In cooling [step 5], cooling is performed to room temperature by water cooling and oil cooling. The cooling rate is, for example, 50°C / s or more. The cooling start temperature is set to 500 to 550°C.
[0070] After the continuous steps of reheating [step 2], hot calendering [step 3], warm calendering [step 4], and cooling [step 5], cold calendering [step 6] is performed. As long as the processing rate of cold calendering [step 6] is more than 90% and the average processing rate of each operation is more than 20%, the conditions can be appropriately selected according to the thickness of the final product plate. When the processing rate is less than 90%, the azimuthal density of β-fiber decreases. In addition, when the average processing rate is less than 20%, the shear deformation of the plate surface increases, and the azimuthal density of β-fiber decreases. In addition, there is no special upper limit of the average processing rate, and the industrial cold calender is about 70%.
[0071] In the aging heat treatment [step 7], a continuous two-stage heat treatment is performed. After the first stage heat treatment, the temperature is lowered to perform the second stage heat treatment, and then cooled to room temperature. The first stage heat treatment is maintained at 400°C or above and 550°C or below for 0.5 hours or more and within 4 hours. The second stage heat treatment is maintained at 150°C or above and 250°C or below for 0.5 hours or more and within 4 hours. The heating rate is 50-200°C / h, and the cooling rate is 100-200°C / h. Regarding the first stage heat treatment, when the temperature is low or the time is short, the precipitation of Cr compounds is insufficient and the conductivity is reduced. Regarding the first stage heat treatment, when the temperature is high or the time is long, the precipitate is easy to coarsen, which will impair the strength. In addition, regarding the second stage heat treatment, when the temperature is low or the time is short, the strain will be excessive, and even after the property adjustment in the low temperature annealing [step 9], the average KAM value will still be too large. Regarding the second stage heat treatment, when the temperature is high or the time is long, the precipitate is easy to coarsen, which will impair the strength.
[0072] Cold rolling [step 8] is performed at a processing rate of 5% or more and 50% or less. When the processing rate is less than 5%, the strength is insufficient. In addition, when the processing rate exceeds 50%, even after the property adjustment by low temperature annealing [step 9], the strain will be excessive and the average KAM value will be too large.
[0073] In low temperature annealing [step 9], heat treatment is performed at a temperature of 200 to 400°C for 10 seconds to 30 minutes, and then cooled to room temperature. The heating rate and cooling rate are 1 to 100°C / s. When the heat treatment temperature is low or the heat treatment time is short, the strain will be excessive and the average KAM value will be too large. When the heat treatment temperature is high or the heat treatment time is long, the precipitates will coarsen and the strength will be impaired.
[0074] According to the above-described embodiment, the copper alloy sheet material has a predetermined alloy composition and the average value of the orientation density of β-fiber is controlled to be high, and can have excellent deep drawing workability and sufficient mechanical strength and electrical conductivity.
[0075] The above embodiments have been described, but the present invention is not limited to the above embodiments, and all aspects included in the concept of the present case and the scope of the patent application can be variously modified within the scope of the present case.
[0076] [Example]
[0077] Next, examples and comparative examples will be described, but the present invention is not limited to these examples.
[0078] (Examples 1 to 23 and Comparative Examples 1 to 11)
[0079] In the melting and casting [step 1], a high-frequency melting furnace is used to melt each alloy component in the atmosphere, and the alloy composition, inevitable impurities, and the plate thickness shown in Table 2 are cast using a mold to obtain a plate having the alloy composition shown in Table 1, unavoidable impurities, and the plate thickness shown in Table 2. Then, the following are continuously performed: heat treatment for more than 1 hour and less than 10 hours in a temperature range of more than 990°C and less than 1050°C [step 2], hot rolling under the conditions shown in Table 2 [step 3], warm rolling [step 4] and cooling [step 5]. Then, plane cutting is performed under the conditions shown in Table 2 to remove the surface oxide film. Then, cold rolling is performed under the conditions shown in Table 2 [step 6]. Then, aging heat treatment is performed under the conditions shown in Table 2 [step 7]. Then, cold rolling is performed under the conditions shown in Table 2 [step 8]. Then, a heat treatment is performed at a heating rate of 1 to 100°C / s and a temperature of 200 to 400°C is maintained for 10 seconds to 30 minutes, and then low-temperature annealing is performed at a cooling rate of 1 to 100°C / s to room temperature [step 9] to obtain a copper alloy sheet having a final sheet thickness shown in Table 2.
[0080] [Table 1]
[0081]
[0082] [Table 2]
[0083]
[0084] [Measurement and evaluation]
[0085] The copper alloy sheets obtained in the above-mentioned Examples and Comparative Examples were subjected to the following measurements and evaluations. The results are shown in Table 3.
[0086] [1] Average value of β-fiber orientation density, maximum value of β-fiber orientation density, average KAM value, and area ratio of regions having atomic planes whose normal to the (100) plane forms an angle of less than 10° with the normal to the copper alloy plate surface (area ratio within 10°) measured by EBSD method
[0087] As EBSD analysis, the measurement part is to set the surface parallel to the rolling direction of the copper alloy plate obtained in the above-mentioned embodiment and comparative example as the surface after mirror finishing by electrolytic grinding, the measurement area is set to 500 μm×500 μm, and the scanning feed is set to 0.2 μm to perform EBSD measurement. The electron beam is set as the field emission electron gun of the field emission scanning electron microscope as the generation source. The probe diameter during measurement is set to about 0.015 μm. The analysis software uses OIM Analysis7 (trade name) made by TSLSolutions Co., Ltd. In addition, in the analysis, the orientation difference of more than 5° is defined as the grain boundary, the measurement point with a reliability index CI value of more than 0.1 and the grain composed of more than 2 pixels are set as the object of analysis, and the Tolerance angle is set to 10°. In addition, the equivalent orientation is included in the analysis of the area ratio of the crystal orientation.
[0088] When the crystal orientation is expressed in Euler angles, Φ 2 The average value of the ODF intensity when the range of φ is 45 to 90° and the random orientation sample is used as the reference is set as the average value of the orientation density of β-fiber measured by the EBSD method. 2 The maximum value of the ODF intensity when the random orientation sample is used as the reference when the range is 45 to 90° is set as the maximum value of the orientation density of β-fiber measured by the EBSD method. In addition, the average value of the KAM values of all analysis object points in the measurement area is set as the average KAM value measured by the EBSD method. In addition, the area ratio of the measurement points where the angle difference between the normal line of the (100) plane of the crystal occupied in the measurement area and the plate surface normal line of the copper alloy plate is less than 10° is set as the area ratio within 10° measured by the EBSD method.
[0089] [2] Tensile strength
[0090] The copper alloy sheets obtained in the above examples and comparative examples were subjected to a tensile test in a direction parallel to rolling using a No. 13B test piece in accordance with JIS Z 2241: 2011. The measured values of two copper alloy sheets (N=2) were averaged to calculate the tensile strength of the copper alloy sheet in a direction parallel to rolling.
[0091] [3] Electrical conductivity
[0092] The electrical conductivity of the copper alloy sheet materials obtained in the above-mentioned examples and comparative examples was measured by a four-terminal method. The electrical conductivity of the copper alloy sheet materials was calculated by averaging the measured values of two copper alloy sheet materials (N=2).
[0093] [4] Drawing test
[0094] A blank with a diameter of 61 mm was produced by pressurizing a copper alloy sheet with a thickness of 0.3 mm, and the blank was drawn with a punch with a diameter of 33 mm. The tip R of the punch was set to 0.50 mm, 0.75 mm, and 1.00 mm. The drawing was performed by applying lubricating oil (R303P) to the copper alloy sheet.
[0095] The evaluation of the punch tip R was graded according to the following criteria. The case where the minimum tip R that was drawn without breaking the copper alloy sheet was 0.50 mm was set as ◎, the case where the minimum tip R that was drawn without breaking the copper alloy sheet was 0.75 mm was set as ○, the case where the minimum tip R that was drawn without breaking the copper alloy sheet was 1.00 mm was set as △, and the case where the copper alloy sheet was broken at any of the above tip Rs was set as ×. Then, when the copper alloy sheet was broken at any of the above tip Rs, the following evaluation on the shape of the drawn part was not performed.
[0096] In addition, regarding the evaluation of the height difference between the apex and the valley of the undulation (the average value of the apex height of the undulation), the classification is performed according to the following criteria. The average of the height difference (average of the apex height - average of the valley height) is 1.00 or more and 1.25 mm or less, and is set as ◎, the average of the height difference is 0.75 mm or more and less than 1.00 mm, and is set as ○, the average of the height difference is 0.25 mm or more and less than 0.75 mm, and the average of the height difference is other than the above, and is set as ×.
[0097] In addition, the standard deviation of the height of the apex of the undulations was classified according to the following criteria: ◎ was set when the standard deviation of the height of the apex of the undulations was 0.1 mm or less, ○ was set when the standard deviation of the height of the apex of the undulations was more than 0.1 and less than 0.2 mm, and × was set when the standard deviation of the height of the apex of the undulations was more than 0.2 mm.
[0098] The test piece having no "×" in either the evaluation of the punch tip R or the evaluation of the average value of the peak height of the undulations was deemed to be passed, and the test piece having "×" in at least one of these evaluations was deemed to be failed.
[0099] [Table 3]
[0100]
[0101] As shown in Tables 1 to 3, in Examples 1 to 23, since the Cr content, the average value of the orientation density of β-fiber, the tensile strength, and the electrical conductivity were controlled within the predetermined ranges, the drawability, mechanical strength, and electrical conductivity were all good.
[0102] Among them, Examples 1 to 4, 6, 8 to 9, and 11 had low average KAM values, and the evaluation of the punch tip R was particularly good. However, in Examples 11 to 12, the processing rate of cold rolling [step 8] was lower than that of these Examples, and the average KAM value after adding strength was lower than the preferred range (0.5° or more), and the strength was slightly low.
[0103] In addition, the average value of the orientation density of β-fiber in Examples 3 to 8, 10, 12 to 23 is particularly preferred, and the evaluation of the average value and standard deviation of the peak height of the undulations of the drawn parts is good. In addition, the cooling start temperature of the cooling [step 5] after the warm rolling [step 4] in Example 9 is lower than that of the other examples, and the aggregation of the plate surface of the (100) plane becomes higher, and the evaluation of the average value and standard deviation of the peak height of the undulations is slightly lower than that of these examples.
[0104] Among the examples, Example 12 has a low Cr content and low strength, but the highest electrical conductivity. On the other hand, Example 21 has a high Cr content and a large amount of accessory components, and has the highest strength, but the electrical conductivity is low.
[0105] On the other hand, in Comparative Example 1, the processing rate of warm rolling [step 4] is low, the average value of the orientation density of β-fiber is low, and the evaluation of the average value of the undulating vertex height is poor. In addition, in Comparative Example 2, the cooling start temperature of cooling [step 5] is high, the average value of the orientation density of β-fiber is low, and the evaluation of the average value of the undulating vertex height is poor. In addition, in Comparative Example 3, the processing rate of cold rolling [step 6] is low, the average value of the orientation density of β-fiber is low, and the evaluation of the average value of the undulating vertex height is poor. In addition, in Comparative Example 4, the heat treatment temperature of the first stage in the aging heat treatment [step 7] is low, and the conductivity is low. In addition, in Comparative Example 5, the heat treatment temperature of the first stage in the aging heat treatment [step 7] is high, and the strength is low. In addition, in Comparative Example 6, the heat treatment temperature of the second stage in the aging heat treatment [step 7] is high, and the strength is low. Furthermore, in Comparative Example 7, the average processing rate of each single operation in cold rolling [Step 6] was low, the average value of the orientation density of β-fiber was low, and the evaluation of the average value of the undulating vertex height was poor. Furthermore, in Comparative Example 8, the processing rate of cold rolling [Step 8] was low, and the strength was low. Furthermore, in Comparative Example 9, the Cr content was low, and the strength was low. Furthermore, in Comparative Example 10, warm rolling [Step 4] was not performed, the average value of the orientation density of β-fiber was low, and the evaluation of the average value of the undulating vertex height was poor. Furthermore, in Comparative Example 11, the Cr content was high, the conductivity was low, and deep drawing could not be performed, and the evaluation of the punch tip R was poor. Therefore, the evaluation of the shape of the drawn parts was not implemented.
Claims
1. A copper alloy sheet having an alloy composition, wherein the alloy composition contains 0.10 mass % or more and 1.00 mass % or less of Cr and the balance is Cu and unavoidable impurities, The average value of the orientation density of β-fiber (Φ2 = 45° to 90°) measured by the EBSD method is 6.0 or more and 10.0 or less. The tensile strength in the direction parallel to the rolling direction is 420 MPa or more and 700 MPa or less. The electrical conductivity is 65% IACS or more and 90% IACS or less.
2. The copper alloy sheet material according to claim 1, wherein: The maximum value of the azimuthal density of the β-fiber is 9.0 or more.
3. The copper alloy sheet material according to claim 1, wherein: The average KAM value measured by the EBSD method is 0.5° or more and 2.0° or less.
4. The copper alloy sheet material according to claim 1, wherein: The area ratio of a region having atomic planes whose normal line to the (100) plane and the normal line to the plate surface of the copper alloy plate material form an angle within 10° as measured by the EBSD method is 10% or less.
5. The copper alloy sheet material according to claim 1, wherein: The alloy composition further contains 0.10 mass % or more and 1.00 mass % or less of one or more elements selected from the group consisting of Mg, Sn, Zn, Fe, Si, and Zr in total.
6. The copper alloy sheet material according to claim 1, wherein: The aforementioned copper alloy sheet is a copper alloy sheet for deep drawing.
7. A drawn part using the copper alloy sheet material according to any one of claims 1 to 6.
Citation Information
Patent Citations
Cu-Cr-Sn-BASED COPPER ALLOY SHEET FOR LEAD FRAME WITH LITTLE RESIDUAL STRESS
JP2013194246A